DETERMINAN BUDAYA BERBAGI PENGETAHUAN DI LINGKUNGAN KERJA PADA KARYAWAN PERUSAHAAN PERTAMBANGAN - Yustinus Yuniarto; Urif Nur Susanto (Universitas Bunda Mulia, 2020)
One important aspect of Knowledge Management is the behavior of sharing knowledge in the work environment. However, it is not easy to implement the culture. The dynamics of competition in the field of Human Resources (HR) is still a major trigger that makes providing information about work closed. This study aims to analyze the determinants of knowledge sharing behavior behavior in the work environment. The Structural Equation Modeling method with SMART PLS 3.0 was used to analyze 100 employees in a tin smelting company in Bangka Belitung Province. This study explains that the desire to share knowledge is not influenced by attitudes, knowledge sharing behavior is not influenced by attitudes, knowledge sharing behavior is not influenced by self-views of the concept of sharing knowledge, the desire to share knowledge is not influenced by social norms. Behavioral factors of knowledge sharing are influenced by the desire to share knowledge, the desire to share knowledge is influenced by the self-view of the concept of sharing knowledge, the behavior of sharing knowledge is influenced by social norms. In the indirect effect, knowledge sharing behavior is not influenced by factors of attitudes and social norms but is influenced by factors of self-view of the concept of sharing. Suggestions for further research can be to test these factors on companies in the sector that have the character of the importance of information knowledge to support jobs such as: banking, insurance, or companies selling smart technology tools. Keywords: knowledge sharing behavior, information, norms